Blocking HIV-1 transmission in the female reproductive tract: from microbicide development to exploring local antiviral responses - Eid, Sahar G (Clin Transl Immunology, 2015)
The majority of new HIV-1 infections are transmitted sexually by penetrating the mucosal barrier to infect target cells. The development of microbicides to restrain heterosexual HIV-1 transmission in the past two decades has proven to be a challenging endeavor. Therefore, better understanding of the tissue environment in the female reproductive tract may assist in the development of the next generation of microbicides to prevent HIV-1 transmission. In this review, we highlight the important factors involved in the heterosexual transmission of HIV-1, provide an update on microbicides' clinical trials, and discuss how different delivery platforms and local immunity may empower the development of next generation of microbicide to block HIV-1 transmission in the female reproductive tract.